Independent Reporting Mechanism (IRM): Cabo Verde Design Report 2018-2020 - Sanches, E. (2021)
Cabo Verde’s first OGP action plan follows recent measures to increase citizens’ access to information and promote transparency and accountability. This includes the creation of new government institutions and the publication of budget information. Cabo Verde is one of Africa’s best performing countries in quality of democracy and governance. While the action plan attempts to address some of these challenges, it would benefit from a clearer connection with OGP values and an increase in civil society involvement in the development process.